On Decolonising Artificial Intelligence - Olojede, Helen Titilola; Fadahunsi, Ayo (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Logic and probability as branches of Mathematics and aspects of Philosophy, underlie and play significant roles in the development of Artificial Intelligence (AI). In its simplest form, logic concerns right reasoning (especially one devoid of fallacies), patent truth and inferences. Probability has to do with uncertainties, that is, the likelihood of an event happening. The divide between traditional AI and modern AI regarding what roles logic and probability play in the development of AI has been mitigated with the notion that both are complementary without displacing the other. While the birth of AI as a field is usually linked to the 1956 conference with figures involving Marvin Minsky and John McCarthy, there are traces of what we refer to as robots, automatons and computations which form the foundation of AI in some non-Western philosophies. To this end, this paper chronicles the emergence of AI in non-Western philosophies, especially in African philosophy and then uses the Yoruba’s ’ifá’ to exemplify the idea of decolonising Al, not forgetting that the basis of ifá itself is logic and, sometimes, probability.